Compressive cyclic ratcheting and fatigue of synthetic, soft biomedical polymers in solution. (February 2016) - Miller, Andrew T.; Safranski, David L.; Smith, Kathryn E.; Guldberg, Robert E.; Gall, Ken
Abstract: The use of soft, synthetic materials for the replacement of soft, load-bearing tissues has been largely unsuccessful due to a lack of materials with sufficient fatigue and wear properties, as well as a lack of fundamental understanding on the relationship between material structure and behavior under cyclic loads. In this study, we investigated the response of several soft, biomedical polymers to cyclic compressive stresses under aqueous conditions and utilized dynamic mechanical analysis and differential scanning calorimetry to evaluate the role of thermo-mechanical transitions on such behavior. Studied materials include: polycarbonate urethane, polydimethylsiloxane, four acrylate copolymers with systematically varied thermo-mechanical transitions, as well as bovine meniscal tissue for comparison. Materials showed compressive moduli between 2.3 and 1900 MPa, with polycarbonate urethane (27.3 MPa) matching closest to meniscal tissue (37.0 MPa), and also demonstrated a variety of thermo-mechanical transition behaviors. Cyclic testing resulted in distinct fatigue-life curves, with failure defined as either classic fatigue fracture or a defined increased in maximum strain due to ratcheting. Our study found that polymers with sufficient dissipation mechanisms at the testing temperature, as evidenced by tan delta values, were generally tougher than those with less dissipation and exhibited ratcheting rather than fatigue fracture much like meniscal tissue. Strain recovery tests indicated that, for some toughened polymers, the residual strain following our cyclic loading protocol could be fully recovered. The similarity in ratcheting behavior, and lack of fatigue fracture, between the meniscal tissue and toughened polymers indicates that such polymers may have potential as artificial soft tissue. Highlights: We tested several soft polymers in cyclic compression in saline to study behavior. DSC and DMA were used to explain the cyclic loading behavior. Polymers devoid of dissipation, as shown by tan delta, exhibited fatigue fracture. Polymers with dissipation remained largely undamaged but showed cyclic ratcheting. Some behave similar to meniscus tissue, suggesting potential as artificial tissue.